Efectividad, seguridad y aplicabilidad clínica de la toxina botulínica tipo a en el tratamiento del bruxismo. revisión sistemática - Lluglla Morales, Kimberly Michelle (2025)
Bruxism is defined as a repetitive activity of the jaw muscles differentiated by grinding or clenching of the dental organs and / or clenching or pushing the jaw. It can have detrimental consequences such as: pain in the masticatory muscles, headaches, tooth wear, sleep disturbances, oral and facial health and aesthetics. Objective: To evaluate the effectiveness, safety and clinical applicability of botulinum toxin type A in the treatment of bruxism by means of a systematic review and thus provide relevant information on this treatment. Methods: Systematic review of scientific articles collected in the online databases PubMed, Wiley and ScienceDirect, using advanced search strings and inclusion and exclusion criteria. Results: A total of 201 scientific articles were collected, of which 16 were chosen as valid for the research. The application of botulinum toxin type A in the treatment of bruxism should be applied to the masseter muscle, with doses varying from 2.5 to 30 units of toxin, being the dentist who selects the appropriate amount. Conclusion: When evaluating the effectiveness, safety and clinical applicability of botulinum toxin type A in the treatment of bruxism, it was determined that it is a more effective treatment than dental splints, being very safe with minimal discomfort such as pain or masticatory problems, the main site of application being the masseter muscle.